Facilitators and barriers to using telepresence robots in aged care settings: A scoping review. (10th January 2022) - Hung, Lillian; Wong, Joey; Smith, Chelsea; Berndt, Annette; Gregorio, Mario; Horne, Neil; Jackson, Lynn; Mann, Jim; Wada, Mineko; Young, Erika
Social isolation has been a significant issue in aged care settings, particularly during the COVID-19 pandemic, and is associated with adverse outcomes, including loneliness, depression, and cognitive decline. While robotic assistance may help mitigate social isolation, it would be helpful to know how to adopt technology in aged care. This scoping review aims to explore facilitators and barriers to the implementation of telepresence robots in aged care settings. Following the Joanna Briggs Institute scoping review methodology and the PRISMA extension for scoping reviews reporting guidelines, we searched relevant peer-reviewed studies through eight databases: CINAHL, MEDLINE, Cochrane, PsychINFO (EBSCO), Web of Science, ProQuest Dissertations and Theses Global, IEEE Xplore, and ACM Digital Library. Google was used to search gray literature, including descriptive, evaluative, quantitative, and qualitative designs. Eligibility includes: studies with people aged 65 years and older who interacted with a telepresence robot in a care setting, and articles written in English. We conducted a thematic analysis to summarize the evidence based on the constructs in the Consolidated Framework of Implementation Research. Of 1183 articles retrieved, 13 were included in the final review. The analysis yielded three themes: relative advantages, perceived risks and problems, and contextual considerations. The key facilitators to telepresence robot adoption are as follows: a feeling of physical presence, ease of use, mobility, and training. The barriers to implementation are as follows: cost, privacy issues, internet connectivity, and workflow. Future research should investigate the role of leadership support in implementation and practical strategies to overcome barriers to technology adoption in aged care settings.